The Role of Driving Actors as Social Engineers in Improving the Community's Economy through Social Entrepreneurship in Marine Ecotourism - Monica Ihsan Alamuiza; Yulhendri Yulhendri; Zul Fahmi (Jurnal Penelitian Pendidikan IPA, 2024)
The gap initiated the movement of empowerment through social entrepreneurship as a business effort to improve the economy of the community in the Sungai Pinang area by a driving actor named Ricky with a learning center known as Ricky's beach house. This research was conducted at Ricky's beach house in the Sungai Pinang marine tourism area with an inductive research approach with a descriptive qualitative method of field study method. This research presents data using descriptive data. This research aims to analyze the role of driving actors in improving the community's economy through social entrepreneurship and marine ecotourism. The results of this study show that the development steps taken by Ricky's beach house by empowering the potential of the surrounding community to be involved in every aspect of the development of Sungai Pinang tourism, such as utilizing people's homes as tourist lodging facilities, turning people into tour guides, and using facilities owned by other residents such as boats for tourists who want to go to the island including at the same time being the captain of the ship, being a waiter at the bar and lounge. The concept of social entrepreneurship also emphasizes the concept of ecotourism where tourism that is developed still pays attention to environmental sustainability even by involving foreign tourists as volunteers.